A slow-release mineralized water treatment tablet capable of dissolving metasilicic acid, a preparation method and application thereof

CN122877899APending Publication Date: 2026-10-09SHANDONG ETERNAL WORLD NEW MATERIAL IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611279010.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0008]本发明的目的在于克服现有技术中偏硅酸矿化材料制备工艺复杂、能耗高、原料受限、生坯成型质量差、偏硅酸溶出不稳定等缺陷,提供一种可溶出偏硅酸的缓释矿化水处理片及其制备方法

Benefits of technology

(1)本发明所用原料硅藻土、稻壳、二氧化硅、沸石、石英等均为常见易得材料,无地域依赖性,原料成本显著低于现有技术中依赖特定矿产或采用纳米抗菌剂、精密造孔剂的方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122877899A_ABST
    Figure CN122877899A_ABST
Patent Text Reader

Abstract

The application provides a slow-release mineralized water treatment piece capable of dissolving metasilicic acid, a preparation method and application thereof, and relates to the technical field of drinking water mineralization materials. The preparation method comprises the following steps: mixing diatomite, rice hull material and alcohol to form a first slurry; performing spray granulation on the first slurry to obtain spray particles; mixing and grinding the spray particles obtained in step S2 with silicon dioxide, zeolite and quartz to form a mixed powder; mixing the mixed powder, a carbonic acid solution and a silica sol to form a wet blank; and performing three-stage press forming on the wet blank to obtain a sheet-shaped green body; and performing secondary drying on the sheet-shaped green body to obtain the slow-release mineralized water treatment piece capable of dissolving metasilicic acid. The application overcomes the defects in the prior art, such as a complex preparation process, high energy consumption, limited raw materials and unstable dissolution of metasilicic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of drinking water mineralization materials technology, specifically to slow-release mineralized water treatment tablets that can release metasilicic acid, their preparation methods, and applications. Background Technology

[0002] Drinking water is an indispensable basic necessity for human survival and development. Its quality not only directly affects individual physiological health but also has a long-term impact on public health as a whole. Therefore, ensuring the safety and quality of drinking water is a crucial project for people's livelihood and a core issue of ongoing concern in scientific research and public health. Among the various components of drinking water, inorganic mineral elements—including macroelements and trace elements—play an irreplaceable and vital role in maintaining normal human physiological functions.

[0003] Metasilicic acid, the main form of silicon dissolved in water, plays a significant role in delaying tissue aging and maintaining structural elasticity. It effectively enhances the elasticity and permeability of blood vessel walls and inhibits lipid deposition on the inner walls of blood vessels, thus softening blood vessels and preventing atherosclerosis, which is of great importance for maintaining cardiovascular health. It is worth noting that the human body cannot synthesize silicon on its own and must rely on external intake. Although natural mineral water is a good source of metasilicic acid, its content is constrained by geological conditions, and the supply is unstable and cannot continuously meet the body's health needs. Therefore, developing a functional material that can stably and controllably dissolve metasilicic acid to achieve precise replenishment of metasilicic acid in drinking water is of significant practical importance.

[0004] Currently, the main methods for preparing metasilicic acid mineralized materials include natural ore leaching, alkali fusion, and chemical synthesis. Natural ore leaching, such as using natural materials like maifanite or silicate minerals, releases minerals through water rinsing, but the release of metasilicic acid is unstable and the release cycle is short. Alkali fusion, such as the method used in Germany, involves burning diatomaceous earth or rice husks at high temperatures and then dissolving the ash in water, followed by impurity removal and concentration; this method is energy-intensive and complex. Chemical synthesis involves the reaction of sodium metasilicate with calcium salts to prepare hydrated calcium silicate, etc., but the raw material costs are high and the process is lengthy.

[0005] In recent years, researchers have proposed various improvement schemes. For example, CN120189911A uses hydrated calcium silicate as the source of metasilicic acid, but the process is lengthy, the pretreatment is complex, and the high-temperature calcination and long soaking time result in a long production cycle and high energy consumption, making it difficult to achieve efficient continuous manufacturing. CN118851793A uses nano-inorganic antibacterial agents and precision pore-forming agents, which significantly increases the cost of raw materials. At the same time, the three-stage temperature-controlled sintering process it relies on has extremely stringent requirements for equipment precision and process control, further limiting the possibility of large-scale promotion. CN118558050A's raw materials are heavily dependent on specific geological minerals in Changbai Mountain, with significant regional limitations; the modification process involves multiple treatment methods such as acids, salts, and gases, and the process is lengthy and uses a large amount of strong acid, bringing potential environmental and safety hazards. The above-mentioned schemes either have problems with complex processes and high energy consumption, or problems with limited raw materials and high costs, or problems with environmental safety risks, making it difficult to meet the comprehensive requirements of preparation efficiency, cost control, and metasilicic acid dissolution performance.

[0006] In addition, existing mineralized materials generally suffer from uneven green density distribution defects during the molding process. Single-stage pressurization or simple multi-stage pressurization can easily lead to a dense surface and a loose core. During the drying process, microcracks are easily generated due to the accumulation of thermal stress, resulting in a decrease in material strength and a shortened service life. Moreover, most existing solutions use high-temperature sintering (600-800℃ and above), which consumes a lot of energy and has stringent equipment requirements.

[0007] Therefore, developing a mineralized material with widely available raw materials, simple preparation process, good molding uniformity, stable and controllable metasilicic acid dissolution, and environmental friendliness remains a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0008] The purpose of this invention is to overcome the shortcomings of existing technologies, such as complex preparation process of metasilicic acid mineralization materials, high energy consumption, limited raw materials, poor green molding quality, and unstable metasilicic acid dissolution, and to provide a slow-release mineralized water treatment sheet that can dissolve metasilicic acid and its preparation method.

[0009] The first aspect of this invention provides a method for preparing a slow-release mineralized water treatment tablet capable of leaching metasilicic acid, the method comprising the following steps: S1: Mix diatomaceous earth, rice husk material and alcohol to form the first slurry; S2: Spray granulation of the first slurry to obtain sprayed particles; S3: The spray particles obtained in step S2 are mixed and ground with silica, zeolite and quartz to form a mixed powder; S4: Mix the powder, carbonic acid solution and silica sol and mold them. Then, press the wet blank in three stages to obtain a sheet-like green blank. S5: The sheet-like green body is dried for the first time to obtain a semi-finished product; S6: The semi-finished product is first soaked in water, and then dried a second time to obtain a slow-release mineralized water treatment tablet that can dissolve metasilicic acid. The three-stage pressure molding process includes the following steps: The first stage involves applying pressure of 10-15 MPa, the second stage 20-30 MPa, and the third stage 50-60 MPa to obtain sheet-like green bodies. A flowchart of the preparation method is available for reference. Figure 1 As shown.

[0010] For example, the pressure applied in the first stage can be any point value or a range between any two points from 10MPa, 11MPa, 12MPa, 13MPa, 14MPa, or 15MPa. The pressure applied in the second stage can be any point value or a range between any two points from 20MPa, 21MPa, 22MPa, 23MPa, 24MPa, 25MPa, 26MPa, 27MPa, 28MPa, 29MPa, or 30MPa. The pressure applied in the third stage can be any point value or a range between any two points from 50MPa, 51MPa, 52MPa, 53MPa, 54MPa, 55MPa, 56MPa, 57MPa, 58MPa, 59MPa, or 60MPa.

[0011] In the preparation process, this application uses a three-stage gradient pressure molding process, which not only ensures that the sheet has sufficient mechanical strength to withstand subsequent operations, but also avoids uneven internal mass and heat transfer caused by excessive thickness. This allows CO2 generated during drying and carbonate decomposition to escape smoothly, forming a uniform open-pore structure and ensuring the long-term stable release capacity of metasilicic acid.

[0012] Specifically, this application employs a three-stage gradient pressure molding process in step S4 to form a uniformly dense green blank from the wet pre-displacement under low pressure, rearrangement under medium pressure, and shaping under high pressure. The first drying step in step S5 removes organic matter while simultaneously forming a porous framework. The immersion treatment in step S6 allows for the controlled hydrolysis of the surface siloxanes into silanol groups, while the second drying eliminates thermal stress and fixes the surface active layer. This synergistic effect of the three steps endows the final product with a gradient functional distribution of highly hydrophilic surface activity and a high-strength internal framework, thereby achieving a sustained-release effect of rapid initial response and stable long-term supply of metasilicic acid.

[0013] Optionally, in step S5, the temperature of the first drying is 90-110℃, and the holding time is 1-3 hours.

[0014] Optionally, in step S6, the temperature of the second drying is 90-110℃, and the holding time is 1-3 hours.

[0015] For example, in step S5, the temperature for the first drying can be any point value or a range between any two points from 90℃, 91℃, 92℃, 93℃, 94℃, 95℃, 96℃, 97℃, 98℃, 99℃, 100℃, 101℃, 102℃, 103℃, 104℃, 105℃, 106℃, 107℃, 108℃, 109℃, or 110℃. In step S6, the temperature for the second drying can be any point value or a range between any two points from 90℃, 91℃, 92℃, 93℃, 94℃, 95℃, 96℃, 97℃, 98℃, 99℃, 100℃, 101℃, 102℃, 103℃, 104℃, 105℃, 106℃, 107℃, 108℃, 109℃, or 110℃.

[0016] Preferably, in step S5, the temperature of the first drying is 95-105℃, and the holding time is 2-3 hours.

[0017] Preferably, in step S6, the temperature of the second drying is 95-105℃, and the holding time is 2-3 hours.

[0018] Optionally, in step S6, the time for immersing the semi-finished product in water is 3-10 seconds. For example, in step S6, the time for immersing the semi-finished product in water can be any value among 3 seconds, 4 seconds, 5 seconds, 6 seconds, 7 seconds, 8 seconds, 9 seconds, or 10 seconds, or a range between any two values.

[0019] Preferably, in step S6, the semi-finished product is immersed in water for 5-8 seconds.

[0020] Optionally, in step S1, the mass ratio of diatomaceous earth to rice husk is (1-3):1. For example, the mass ratio of diatomaceous earth to rice husk can be any ratio of 1:1, 2:1 or 3:1.

[0021] Optionally, in step S3, the mass ratio of spray particles, silica, zeolite and quartz is (5-8):(2-5):(1-2):(1-2), preferably 6:3:1.5:1.5.

[0022] Optionally, in step S4, the mass ratio of the mixed powder, carbonic acid solution and silica sol is 10:(3-5):(1-2), preferably 10:4:1.5.

[0023] Optionally, in step S4, the diameter of the sheet-like green blank is 40-45 mm, the thickness is 8-12 mm, and the diameter-to-thickness ratio is (3.3-5.6):1.

[0024] Optionally, the concentration of the carbonic acid solution is 10-20 wt%. For example, the concentration of the carbonic acid solution can be any point value or a range between any two points from 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, or 20 wt%.

[0025] Optionally, the silica sol concentration is 5-10 wt%. For example, the silica sol concentration can be any point value or a range between any two points from 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%.

[0026] The second aspect of the present invention provides a slow-release mineralized water treatment tablet that can dissolve metasilicic acid. Using 250 mL of pure water as a circulation unit, a continuous cyclic immersion test is conducted. After a total of 200 cycles, the concentration of metasilicic acid dissolved is not less than 1 mg / L.

[0027] The third aspect of this invention provides the application of a slow-release mineralized water treatment sheet capable of leaching metasilicic acid in the preparation of drinking water treatment filter cartridges.

[0028] Compared with the prior art, the present invention achieves at least one of the following beneficial effects: (1) The raw materials used in this invention, such as diatomaceous earth, rice husk, silica, zeolite, and quartz, are all common and readily available materials with no regional dependence. The cost of raw materials is significantly lower than that of existing technologies that rely on specific minerals or use nano-antibacterial agents or precision pore-forming agents.

[0029] (2) This invention employs a three-stage gradient pressurization strategy: low-pressure pre-sorting, medium-pressure rearrangement, and high-pressure shaping. The first stage (10-15 MPa) of low pressure causes the particles in the wet billet to initially slip and guides the residual gas inside to slowly escape along the mold wall, effectively avoiding the gas being trapped inside the billet due to the instantaneous impact of high pressure. The second stage (20-30 MPa) promotes the uniform spread of silica sol and carbonic acid solution between particles and forms flexible bonding bridges. The third stage (50-60 MPa) of high pressure holding enhances the synergistic effect of mechanical interlocking and chemical bonding between particles. After this gradient pressurization, the density difference of the green billet in the thickness direction can be controlled within a very small range, completely solving the common defect of "dense surface and loose core" in single-stage pressurization, and significantly improving the demolding qualification rate. Meanwhile, high-pressure holding ensures that the silica sol fully fills the multi-level gaps between the sprayed particles and the powder, giving the green body high initial compressive strength (wet strength), sufficient to withstand vibration and collision during demolding, transfer, and automated stacking by robotic arms, thus guaranteeing a high yield for continuous industrial production. During gradient pressurization, the carbonic acid solution is uniformly squeezed into the gaps between particles, and the holding pressure stage causes it to form an "isolation layer" rather than an "agglomerated phase" within the green body. This provides a spatial basis for the uniform escape of CO2 gas during subsequent drying, avoiding localized concentrated gas generation that could lead to expansion and cracking of the green body.

[0030] (3) The present invention only requires drying at 90-110℃, without high-temperature sintering (the prior art usually requires 600-800℃ and above), which greatly reduces energy consumption and equipment requirements. The entire preparation process only uses alcohol and carbonic acid solution, without strong acids and other dangerous chemicals, making it environmentally friendly and highly safe.

[0031] (4) The present invention utilizes instantaneous surface hydration and secondary isothermal stabilization processes: During the first drying process, amorphous SiO2 shrinks, accumulating radial thermal stress inside the semi-finished product. When the semi-finished product is immersed in water for 3-10 seconds, water molecules instantly wet the surface and near-surface micropores, causing uniform micro-expansion of the surface through capillary action. This expansion stress is vector-canceled with the original thermal stress. Subsequently, during the secondary drying process, the stress is uniformly released as water molecules are slowly removed, effectively inhibiting the initiation and propagation of microcracks. This improves the bending strength of the semi-finished product compared to the first drying process, and delay cracking no longer occurs during storage. Simultaneously, the extremely short immersion time of approximately 3-10 seconds ensures that water molecules act only on the surface pore walls (with controllable penetration depth), prompting the controlled hydrolysis of the inert siloxanes (≡Si-O-Si≡) formed during the first drying stage, transforming them into highly active silanol groups (≡Si-OH). Meanwhile, the original porous framework and silicon source crystal phase structure of the internal core region are completely preserved. This achieves a gradient functional distribution of "high surface hydrophilic activity and high internal strength framework," exhibiting a synergistic advantage of "fast initial response and stable long-term supply" during metasilicic acid dissolution. After the second drying, the silanol groups on the surface of the semi-finished product are in a stable associated state, and the total water absorption rate is controlled at an extremely low level. This treatment prevents the intermediate from absorbing moisture and softening or surface powdering under normal storage conditions (temperature and humidity fluctuations), significantly extending its shelf life, facilitating batch-to-batch quality consistency control, and reducing the stringent dependence of production scheduling on the drying endpoint.

[0032] (5) In the immersion test, the slow-release mineralized water treatment tablets prepared by the present invention were continuously immersed in 250 mL of pure water as one cycle unit. After a total of 200 cycles, the concentration of metasilicic acid leached from the water treatment tablets in pure water was still not less than 1 mg / L. Preferably, from the 10th cycle to the 200th cycle, the decay rate of the metasilicic acid leaching concentration was 0.62-0.64, demonstrating excellent initial rapid response capability and long-term stable release capability. Attached Figure Description

[0033] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings: Figure 1 An exemplary embodiment of the process flow diagram for preparing the slow-release mineralized water treatment tablets that can dissolve metasilicic acid according to the present invention is shown; Figure 2 An exemplary embodiment is shown, which is a side view of the slow-release mineralized water treatment tablet product containing soluble metasilicic acid prepared according to Example 1 of the present invention. Figure 3 An exemplary embodiment is shown, illustrating the front view of the slow-release mineralized water treatment tablet product containing soluble metasilicic acid prepared according to Example 1 of the present invention. Detailed Implementation

[0034] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0035] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially.

[0036] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.

[0037] Example 1 In an exemplary embodiment of the present invention, a method for preparing a slow-release mineralized water treatment tablet capable of leaching metasilicic acid includes the following steps: S1. Mixing and Pulping: Mix 8 parts by weight of diatomaceous earth, 5 parts by weight of ground rice husk material, and 75% alcohol, and form a slurry by wet grinding. Wet grinding ensures that the raw materials are fully refined and mixed, thereby improving the reactivity.

[0038] S2. Spray granulation: The slurry obtained in step S1 is atomized to form uniform microspheres with a particle size of 0.4 mm. This process generates a large number of pores on the particles (pores left by alcohol evaporation) and improves fluidity, facilitating subsequent mixing and molding.

[0039] S3. Mixing and Stirring: Mix 8 parts by weight of the sprayed particles obtained in step S2 with 5 parts by weight of silica, 2 parts by weight of zeolite, and 2 parts by weight of quartz powder, and stir thoroughly. Mix and refine the sprayed particles and powder to ensure uniform distribution of each component, construct a composite silicon source system, and achieve continuous dissolution of metasilicic acid.

[0040] S4. Molding: The mixed powder from step S3 is placed into a rolling pelletizing machine, and 10 parts by weight of carbonic acid solution (15wt%) and 3 parts by weight of silica sol (8wt%) are added and mixed to obtain a wet blank. The wet blank is placed into a molding die and subjected to three-stage pressure molding: the first stage is pressurized at 12MPa to cause initial slippage of the particles in the wet blank and guide the residual gas inside to slowly escape along the die wall; the second stage is pressurized at 25MPa to promote the uniform spread of silica sol and carbonic acid solution between the particles and form flexible bonding bridges; the third stage is pressurized at 55MPa and held for 30 seconds to enhance the synergistic effect of mechanical interlocking and chemical bonding between the particles. After demolding, a sheet-like green blank is obtained, which has a diameter of 42mm, a thickness of 10mm, and a diameter-to-thickness ratio of 4.2:1.

[0041] S5. First drying: Place the sheet-like green body obtained in step S4 into a forced-air drying oven and dry it at 100℃ for 2 hours, then cool it to room temperature. Drying removes organic matter from the rice husk material, promotes the decomposition of carbonates to produce CO2 and form pores, and softens and binds the amorphous SiO2 portion, but avoids excessive densification to maintain the porosity and activity of the material.

[0042] S6. Immersion and Second Drying: Immerse the semi-finished product obtained in step S5 in water for 5 seconds, take it out and dry it again at 100°C for 2 hours, and then cool it to room temperature to obtain a slow-release mineralized water treatment tablet that can dissolve metasilicic acid. Figure 2 The side view of the slow-release mineralized water treatment tablet product containing soluble metasilicic acid prepared in this embodiment is shown. Figure 3 The image shows the front view of a slow-release mineralized water treatment tablet product that can dissolve metasilicic acid.

[0043] The slow-release mineralized water treatment tablets prepared in Example 1 were subjected to dynamic service life testing. Test method: At room temperature, one water treatment tablet prepared in Example 1 was placed in 250 mL of pure water and allowed to soak for 30 minutes. The tablet was then removed, and the concentration of metasilicic acid in the soaking solution was measured. Subsequently, sampling and testing were performed every 10 cycles (i.e., sampling and testing after the 10th, 20th, 30th…200th cycle). For the remaining cycles, only fresh pure water was used, and the soaking process was repeated. After each sampling, the old soaking solution was discarded, and 250 mL of pure water was added again to continue the next cycle. This continuous cyclical operation was performed until a total of 200 cycles were completed. The test results are shown in Table 1.

[0044] Table 1

[0045] As shown in Table 1, the metasilicic acid dissolution of the slow-release mineralized water treatment tablets prepared in Example 1 reached 4.665 mg / L in the initial stage (first cycle) of 200 cycles and remained at 1.137 mg / L after 200 cycles. The water quality indicators (pH, TDS, turbidity) remained generally stable, indicating that the slow-release mineralized water treatment tablets prepared in this invention have good long-term slow-release performance and water quality safety.

[0046] Example 2 The difference from Example 1 is as follows: in step S1, the mass ratio of diatomaceous earth to rice husk is 3:1; in step S3, the mass ratio of sprayed particles, silica, zeolite, and quartz is 8:4:2:2; in step S4, the mass ratio of mixed powder, carbonic acid solution, and silica sol is 10:5:2; in step S4, the diameter of the sheet green body is 45 mm, the thickness is 12 mm, and the diameter-to-thickness ratio is 3.75:1; and in step S6, the soaking time is 3 seconds. The remaining steps and parameters are the same as in Example 1.

[0047] Example 3 The difference from Example 1 is as follows: in step S1, the mass ratio of diatomaceous earth to rice husk is 1:1; in step S3, the mass ratio of sprayed particles, silica, zeolite, and quartz is 5:2:1:1; in step S4, the mass ratio of mixed powder, carbonic acid solution, and silica sol is 10:3:1; in step S4, the diameter of the sheet green body is 40 mm, the thickness is 8 mm, and the diameter-to-thickness ratio is 5:1; and in step S6, the soaking time is 10 seconds. The remaining steps and parameters are the same as in Example 1.

[0048] Example 4 The difference from Example 1 is that: in step S5, the first drying temperature is 90°C and the holding time is 3 hours; in step S6, the second drying temperature is 90°C and the holding time is 3 hours. The remaining steps and parameters are the same as in Example 1.

[0049] Example 5 The difference from Example 1 is that: in step S5, the first drying temperature is 110°C and the holding time is 1 hour; in step S6, the second drying temperature is 110°C and the holding time is 1 hour. The remaining steps and parameters are the same as in Example 1.

[0050] Example 6 The difference from Example 1 is that: in step S5, the first drying temperature is 100°C and the holding time is 1 hour; in step S6, the second drying temperature is 150°C and the holding time is 1 hour. The remaining steps and parameters are the same as in Example 1.

[0051] Example 7 The difference from Example 1 is that: in step S5, the first drying temperature is 150°C and the holding time is 1 hour; in step S6, the second drying temperature is 100°C and the holding time is 1 hour. The remaining steps and parameters are the same as in Example 1.

[0052] Example 8 The difference from Example 1 is that the pressures of the three-stage pressurization in step S4 are 10MPa, 20MPa, and 50MPa, respectively, and the pressure holding time is 40 seconds. The remaining steps and parameters are the same as in Example 1.

[0053] Example 9 The difference from Example 1 is that the pressures of the three-stage pressurization in step S4 are 15MPa, 30MPa, and 60MPa, respectively, and the pressure holding time is 20 seconds. The remaining steps and parameters are the same as in Example 1.

[0054] Example 10 The difference from Example 1 is that in step S6, the semi-finished product is immersed in water for 20 seconds.

[0055] Comparative Example 1 Based on Example 1, the main difference is that single-stage pressure molding is used in step S4, that is, pressure is applied at 55 MPa once and held for 30 seconds, without gradient pressure. The remaining steps and parameters are the same as in Example 1.

[0056] Comparative Example 2 Based on Example 1, the main difference is that step S4 uses a two-stage pressure molding process, that is, after applying pressure of 12MPa, pressure is directly applied at 55MPa and held for 30 seconds, omitting the intermediate second stage of pressure application. The remaining steps and parameters are the same as in Example 1.

[0057] Comparative Example 3 Based on Example 1, the main difference is that step S4 uses a two-stage pressure molding process, that is, after applying pressure of 12MPa, pressure is directly applied at 25MPa and held for 30 seconds, omitting the intermediate third-stage pressure application. The remaining steps and parameters are the same as in Example 1.

[0058] Comparative Example 4 Based on Example 1, the main difference is that in step S6, the water is not soaked and the second drying is carried out directly. The remaining steps and parameters are the same as in Example 1.

[0059] Test case Dynamic service life tests were conducted on the slow-release mineralized water treatment tablets prepared in the above embodiments and comparative examples. The test method was the same as in Example 1. The amount of metasilicic acid leaching and the appearance of the water tablets (whether there were cracks, powdering, etc.) were recorded after 200 cycles. The results are shown in Table 2.

[0060] The quantitative characterization of the dissolution stability of metasilicic acid was performed using the "dissolution decay rate" index, i.e., (concentration at 10th reaction - concentration at 200th reaction) / concentration at 10th reaction. The smaller this value, the better the sustained-release stability. The dissolution decay rate data for each example and comparative example are shown in Table 2.

[0061] Table 2

[0062] Referring to Table 2, this application ensures uniform green body density and structural integrity through a three-stage gradient pressure molding process. First, low-temperature drying preserves the porous active framework of the material. Then, a second drying process following a 3-10 second immersion in water activates the surface layer and eliminates stress. Preferably (refer to Examples 1-5), the final prepared slow-release mineralized water treatment tablets exhibit a metasilicic acid dissolution concentration ≥1 mg / L in 200 cyclic immersion tests, with a dissolution attenuation rate ≤0.64. The tablets have a smooth, intact appearance, free of cracks and delamination. This demonstrates that the present invention effectively overcomes the technical defects of the prior art, such as poor green body molding quality, thermal stress cracking, and unstable metasilicic acid dissolution, achieving long-term stable release of metasilicic acid.

[0063] Compared with Example 1, when using single-stage pressurization (Comparative Example 1) or two-stage pressurization (Comparative Examples 2 and 3), the metasilicic acid dissolution concentration of the water flakes after 200 cycles was less than 1 mg / L, and defects such as layering, uneven density, or overall looseness were observed in the appearance. This indicates that the three-stage gradient pressurization method of low-pressure pre-drainage, medium-pressure rearrangement, and high-pressure shaping effectively solves the common defects of dense surface and loose core found in single-stage or two-stage pressurization, ensuring uniform density and structural integrity of the green body, thereby significantly improving the long-term dissolution performance of metasilicic acid.

[0064] Compared with Example 1, when the immersion treatment was omitted, the metasilicic acid dissolution concentration after 200 cycles was 0.943 mg / L (less than 1 mg / L), and the water sheet showed delayed microcracks after storage, with a dissolution attenuation rate of 0.69. This indicates that an extremely short immersion treatment of 3-10 seconds can controllably hydrolyze the surface siloxane into highly active silanol groups, while simultaneously offsetting internal thermal stress through capillary micro-expansion, achieving a gradient functional distribution of high surface hydrophilic activity and a high-strength internal framework, thereby endowing the material with sustained-release characteristics of fast initial response and stable long-term supply. Referring to Example 10, when the immersion time was extended to 20 seconds, the metasilicic acid dissolution concentration decreased to 0.813 mg / L, the attenuation rate increased to 0.73, and slight peeling appeared on the surface of the water sheet, indicating that excessively long immersion time would cause water to penetrate into the interior of the material, destroying the internal framework structure and affecting the sustained-release performance of metasilicic acid.

[0065] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.

Claims

1. A method for preparing a slow-release mineralized water treatment tablet capable of soluble metasilicic acid, characterized in that, The preparation method includes the following steps: S1: Mix diatomaceous earth, rice husk material and alcohol to form the first slurry; S2: Spray granulation of the first slurry to obtain sprayed particles; S3: The spray particles obtained in step S2 are mixed and ground with silica, zeolite and quartz to form a mixed powder; S4: Mix the powder, carbonic acid solution and silica sol and mold them. Then, press the wet blank in three stages to obtain a sheet-like green blank. S5: The sheet-like green body is dried for the first time to obtain a semi-finished product; S6: The semi-finished product is first soaked in water, and then dried a second time to obtain a slow-release mineralized water treatment tablet that can dissolve metasilicic acid. The three-stage pressure molding process includes the following steps: The first stage involves applying pressure of 10-15 MPa, the second stage involves applying pressure of 20-30 MPa, and the third stage involves applying pressure of 50-60 MPa to obtain sheet-like green bodies.

2. The preparation method according to claim 1, characterized in that, In step S5, the temperature of the first drying is 90-110℃, and the holding time is 1-3 hours; And / or in step S6, the temperature of the second drying is 90-110°C, and the holding time is 1-3 hours.

3. The preparation method according to claim 2, characterized in that, In step S5, the temperature of the first drying is 95-105℃, and the holding time is 2-3 hours; In step S6, the temperature of the second drying is 95-105°C, and the holding time is 2-3 hours.

4. The preparation method according to claim 1, characterized in that, In step S6, the semi-finished product is immersed in water for 3-10 seconds.

5. The preparation method according to claim 4, characterized in that, In step S6, the semi-finished product is immersed in water for 5-8 seconds.

6. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of diatomaceous earth to rice husk material is (1-3):1; And / or in step S3, the mass ratio of spray particles, silica, zeolite and quartz is (5-8):(2-5):(1-2):(1-2); And / or in step S4, the mass ratio of the mixed powder, the carbonic acid solution and the silica sol is 10:(3-5):(1-2).

7. The preparation method according to claim 1, characterized in that, In step S3, the mass ratio of spray particles, silica, zeolite, and quartz is 6:3:1.5:1.5; In step S4 and / or step S5, the mass ratio of the mixed powder, the carbonic acid solution, and the silica sol is 10:4:1.

5.

8. The preparation method according to claim 1, characterized in that, In step S4, the diameter of the sheet green blank is 40-45 mm, the thickness is 8-12 mm, and the diameter-to-thickness ratio is (3.3-5.6):

1.

9. A slow-release mineralized water treatment tablet containing soluble metasilicic acid prepared by the preparation method according to any one of claims 1-8, characterized in that, Using 250mL of pure water as a circulation unit, the continuous immersion test was conducted. After a total of 200 cycles, the concentration of metasilicic acid leaching was not less than 1 mg / L.

10. The application of a slow-release mineralized water treatment sheet capable of leaching metasilicic acid as described in claim 9 in the preparation of drinking water treatment filter cartridges.

Citation Information

Patent Citations

  • Composite filter material and mineralization filter element capable of simulating quality of underground water in Changbai Mountain

    CN118558050A

  • Antibacterial ceramic filter material, preparation method and application thereof, and filter element

    CN118851793A

  • Modification method of filter element raw material, modified filter element raw material, mineralized filter material, mineralized filter element and preparation method of mineralized filter element

    CN120189911A